Effect of roasting in electric oven on oil quality and residue from Cucurbita maxima (Marina di Chioggia) and Cucurbita pepo (Calabaza Mercado Verde) seeds from Morocco - Boujemaa, Ihssan; El Bernoussi, Sara; El Guezzane, Chakir; Maggi, Filippo; Caprioli, Giovanni; Bouyahya, Abdelhakim *; Harhar, Hicham; Tabyaoui, Mohamed (Elsevier, 2024)
This study aimed to assess the impact of the roasting process, conducted in an electric oven, on the oil quality and residue derived from two pumpkin seed species, namely Cucurbita maxima (C. maxima) and Cucurbita pepo (C. pepo), cultivated in Morocco. The seeds underwent roasting at temperatures of 60, 90, 120, and 150 °C for 45 min. The cold press extracted oils were characterize in terms of fatty acids, phytosterols, tocopherols and pigment content meanwhile phenolic content and antioxidant activity were evaluated in the residues. The heat treatment did not significantly affect fatty acid content; however, it affected sterols, particularly β-sitosterol, which experienced an 8 % decrease in C. maxima. Instead, total sterols significantly increased in C. pepo from 153.84 to 181.71 mg/100g. Moreover, the heat treatment influenced the tocopherol contents, revealing a substantial increase in both species. Phenolic content was significantly affected in C. pepo whereas the variation in C. maxima was statistically nonsignificant. Antioxidant activity exhibited fluctuations during the heat treatment, resulting in an overall increase in the oils. The roasting process influences the composition of bioactive compounds and antioxidant activity in pumpkin seed oil. These findings contribute to a deeper exploration of the functional properties of pumpkin seed products.